Microstructural analysis of quartz grains in Vasyugan suite sandstones of layer U[1]{1-2} in Kazanskoe deposit; IOP Conference Series: Earth and Environmental Science; Vol. 21: XVIII International Scientific Symposium in Honour of Academician M. A. Usov: Problems of Geology and Subsurface Development 7–11 April 2014, Tomsk, Russia - Cherdantseva D. (Mineralogy, Geochemistry and Petrography, 2014)
Title screen